Erythromelanosis Follicularis Faciei et Colli: A Case Report in a Caucasian Male and Brief Review of the Literature - Carl Maximilian Thielmann; Wiebke Sondermann (Karger Publishers, 2020)
Erythromelanosis follicularis faciei et colli, a rare condition of unknown etiology, was first described by Kitamura et al. from Japan in 1960. It is characterized by a triad consisting of well-demarcated erythema, hyperpigmentation, and follicular papules. We report the case of a 50-year-old Caucasian male, who had asymptomatic symmetrical facial lesions since the age of 42. His family history was unremarkable. Published erythromelanosis follicularis faciei et colli cases of the last 10 years are summarized in this report to demonstrate the variability and differences in the clinical presentation of this uncommon diagnosis.